2013
DOI: 10.1161/strokeaha.111.000590
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Length of Hospitalization in Patients Admitted With Transient Ischemic Attack in United States

Abstract: Background and Purpose-Approximately 70% of all patients presenting with transient ischemic attack are admitted to the hospital in United States. The duration and cost of hospitalization and associated factors are poorly understood. This article seeks to identify the proportion and determinants of prolonged hospitalization and to determine the impact on hospital charges using nationally representative data. Methods-We determined the national estimates of length of stay, mortality, and charges incurred in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 19 publications
3
19
1
Order By: Relevance
“…In the Netherlands, the LOS was the same, but the costs were higher (US$3,474) 16 . In the USA, the LOS was also the same but the costs were even higher (US$16,450) 26 . In this USA study, the author reported that the treatment of TIA comorbidities, the characteristics of hospitals and health insurance increased the LOS and cost of hospitalization.…”
Section: Discussionmentioning
confidence: 89%
“…In the Netherlands, the LOS was the same, but the costs were higher (US$3,474) 16 . In the USA, the LOS was also the same but the costs were even higher (US$16,450) 26 . In this USA study, the author reported that the treatment of TIA comorbidities, the characteristics of hospitals and health insurance increased the LOS and cost of hospitalization.…”
Section: Discussionmentioning
confidence: 89%
“…A prospective analysis of 515 stroke patients (Copenhagen Stroke Study), showed that outcome measures such as the activities of daily living (measured by the Barthel Index [BI]) were significantly worse in older patients, although neurological outcomes were not affected by age (Nakayama et al 1994), suggesting a poorer ability to compensate among this older population. Furthermore, hospitalization length was significantly increased in older patients (>65 yrs) with stroke (Qureshi et al 2013). Observational studies in university-hospital settings reported that age was a highly significant predictor of poor functional outcome (Knoflach et al 2012, Denti et al 2010, Abanto et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is also interesting to compare the costs of psychiatric hospitalization to those for common general medical disorders. For example, recent cost-estimates of hospitalization for stroke have averaged 21.8 (CI: 4.70-39.0), and for a heart attack or comparable cardiac illness, 27.3 (8.75-35.8) thousands of US dollars, or 2.3-2.9-times more than the average cost of psychiatric hospitalization at the present study site, 9.50 (8.86-10.1) [58][59][60].…”
Section: Discussionmentioning
confidence: 63%